Multinationals, Foreign Market Entry, and Employment Security - Daniel Baumgarten; Ronald Bachmann; Joel Stiebale (Verein für Socialpolitik, 2010)
We analyze how foreign direct investment (FDI) affects employment security. Using administrative micro data for German employees allows us to follow individual workers over time. FDI intensity is measured at the sectoral level, which enables us to take into account direct as well as indirect (spillover) effects of FDI. Furthermore, we are able to account for both inward and outward FDI and to distinguish between FDI at the intensive margin and FDI at the extensive margin in the form of Greenfield investments and foreign acquisitions. We are also able to investigate whether specific worker groups are affected differently by FDI. Our main finding is that both inward and outward FDI significantly increases employment security. Important exceptions are very young and old workers, who are negatively affected. These results seem to be mainly driven by the intensive margin.
Keywords: F21; F23; J63; 330; foreign direct investment; labour market transitions; duration analysis